Consideration of heterogeneity in the fragmentation of carbonate reservoir deposits in the modeling of acid treatments - Mukhametshin Vyacheslav Sh.; Gilyazetdinov Ruslan; Khamzin Rinat (E3S Web of Conferences)
The work is devoted to an integral assessment of the prospects for using a modified system for determining the dynamics of changes in heterogeneity coefficients based on the thickness properties of deposits confined to the carbonate reservoirs of the Bashkir-Serpukhov deposits. According to the object of study under consideration, the low effectiveness of various types of hydrochloric acid effects on the formation has been established, which is due to the complex structure of the void space and a number of factors that reduce the penetration depth of the composition and at the same time increase the neutralization time of the compositions. Using empirical models, the values of heterogeneity in dissection for four compositions widely used in the considered geological and physical conditions are calculated. The criteria for their application are determined based on the influence of thickness properties, which will make it possible to make effective management decisions. It is concluded that it is necessary to build complex models for full-fledged computer modeling of hydrochloric acid effects on the reservoir.